2019
DOI: 10.1016/s2214-109x(19)30104-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for cleft lip and palate in low-resource settings: a case-control study

Abstract: Background Cleft lip with or without palate is the most common birth defect with a global prevalence of 1 in 700 births. Although there is a clear algorithm of care in developed countries, the lack of access to surgery in low-income and middle-income countries (LMICs) means that millions of people live with this easily treated condition. Although smoke exposure from unsafe cooking practices no longer occurs in the developed world and is not routinely studied, exposure to smoke from cooking remains an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Exposure to cooking fire smoke has recently been indicated as a risk factor for OFC, potentially larger than active or passive tobacco smoke exposure. 39 Nearly 85% of the SFG parents reported maternal exposure to cooking fire smoke either inside the house, outside the house, in a kitchen separated from the house, or some combination of the three. This is corroborated by one estimate that 87% of all energy used in Alta Verapaz is generated by firewood.…”
Section: Sfg Cohort and Potential Risk Factorsmentioning
confidence: 99%
“…Exposure to cooking fire smoke has recently been indicated as a risk factor for OFC, potentially larger than active or passive tobacco smoke exposure. 39 Nearly 85% of the SFG parents reported maternal exposure to cooking fire smoke either inside the house, outside the house, in a kitchen separated from the house, or some combination of the three. This is corroborated by one estimate that 87% of all energy used in Alta Verapaz is generated by firewood.…”
Section: Sfg Cohort and Potential Risk Factorsmentioning
confidence: 99%
“…There are no substantial African studies demonstrating the association between air pollutants and CLP risk. Related African studies have focused on socioeconomic status, educational level, cigarette smoking, alcohol consumption, indoor cooking with charcoal, and the use of multivitamins, among other factors [42][43][44]. Data collection on air quality in several Sub-Saharan African countries is reportedly insufficient to inform science-driven health research [45].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have demonstrated that the etiology of OFC is both polygenic and multifactorial in nature. [5][6][7][8][9][10] The prevalence of cleft anomalies vary widely according to gender, 11,12 socioeconomic status, 13 ancestry, 4 maternal nutrition, 14 and environmental determinants such as prenatal exposure to tobacco and other teratogenic agents. [15][16][17] Corrective treatment of cleft lip with or without palate involves extensive multispecialty longitudinal assessment and management.…”
Section: Introductionmentioning
confidence: 99%